A POSSIBLE ELEMENTARY MODEL FOR EARLY DETECTION OF MACROECONOMIC IMBALANCES IN MACEDONIA - Popovski, Nikola (International Scientific Journal Vision, 2017)
Predicting the economic crises or existence of macroeconomic imbalances is very useful for national economies. There are many academic and institutional efforts to make it more efficient. One of it is the EU Commission model based on Alert Mechanism Report which aims to identify and address imbalances that hinder the smooth functioning of the economies of EU. Based on it and some other academic experiences and researches made, the Macedonian elementary model for early detection of macroeconomic imbalances is developed using 15 macroeconomic, fiscal, monetary, finance and external economy indicators grouped in 4 main indicators which are the base for calculation of index as an aggregate (basic) indicator for detecting macroeconomic imbalances based on weighted values. The model is constructed using the very characteristics of Macedonian economy and could be used to lunch activities to prevent further and deeply imbalances or possible recession in the economy.